2010
DOI: 10.1038/onc.2010.129
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic alterations and gene expression profiles in respiratory epithelia exposed to cigarette smoke condensate

Abstract: Limited information is available regarding epigenomic events mediating initiation and progression of tobacco-induced lung cancers. In this study, we established an in vitro system to examine epigenomic effects of cigarette smoke in respiratory epithelia. Normal human small airway epithelial cells and cdk-4/hTERT-immortalized human bronchial epithelial cells (HBEC) were cultured in normal media with or without cigarette smoke condensate (CSC) for up to 9 months under potentially relevant exposure conditions. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
214
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(231 citation statements)
references
References 49 publications
11
214
0
1
Order By: Relevance
“…Consistent with our observations in the SAE, several studies have demonstrated that cigarette smoke in vivo and in vitro can mediate differences in the methylation status of individual genes in lung cells as well as non-lung cells. For example, immortalized human bronchial epithelial cells (HBECs) exposed to cigarette smoke extract display hypermethylation in association with tumor suppressor genes such as (RASSF1A) and retinoic acid receptor b2 (RARb2) in a dose-dependent manner (14). For RASSF1A, the increase in DNA methylation correlated with a decrease in gene expression.…”
Section: Smoking-associated Changes In Lung Dna Methylationmentioning
confidence: 99%
“…Consistent with our observations in the SAE, several studies have demonstrated that cigarette smoke in vivo and in vitro can mediate differences in the methylation status of individual genes in lung cells as well as non-lung cells. For example, immortalized human bronchial epithelial cells (HBECs) exposed to cigarette smoke extract display hypermethylation in association with tumor suppressor genes such as (RASSF1A) and retinoic acid receptor b2 (RARb2) in a dose-dependent manner (14). For RASSF1A, the increase in DNA methylation correlated with a decrease in gene expression.…”
Section: Smoking-associated Changes In Lung Dna Methylationmentioning
confidence: 99%
“…In vitro exposure of airway epithelial cells or immortalized bronchial epithelial cells to CS condensate/ extract (oxidants) reduced H4K16ac and H4K20me3, but increased H3K27me3. This may have implications in tumor development in several cancer types associated with tobacco smoking (77). It is well known that COPD is associated with a significantly increased incidence of lung cancer and other comorbidities in susceptible chronic smokers.…”
Section: Histone Methyltransferasementioning
confidence: 99%
“…Transcriptional silencing of genes by CpG island (CGI) methylation is now recognized as a critical component in initiation and progression of lung cancer (Kerr et al, 2007;Kim et al, 2007;Na et al, 2010;Toyooka et al, 2001). In addition, variation in methylation status has been associated with tobacco smoking (Liu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%